A Phenomenological Study of Marriage Postponement Among Generation Z - Windy Adiska Irani; Muhamad Habibullah AR (LP3M KH Yazid Karimullah Institute, 2025)
The era of globalization has changed many things, including generation Z's mindset about marrdiage. Many of generation Z feel safe when postponing marrdiage. This is clearly contrary to Islamic law, where Islam strongly recommends its followers to have a partner because by having a partner, peace of mind can be obtained besides By entering into marrdiage, someone can avoid committing adultery. This research is qualitative research or field research using observation and interviews in a semi-structured form where the researcher tries to conduct interviews from one person and then develops into many people. The results of the research state that postponing marrdiage is permitted in Islam for Shardia reasons, whereas based on the results of the author's interviews with sources, the main reasons for generation Z not getting married are 1) making their parents happy, 2) trust issues, 3) financdial, 4) education.